The reluctant warrior - Connealy, Mary (High Sierra sweethearts, 2018)
"In 1860s Lake Tahoe, Cameron Scott reunites with his daughter and nephew but has lost their trust. When he's hurt protecting them, the stubborn but beautiful Gwen Harkness is his caretaker. As she helps him win back their hearts, he finds himself wanting to win hers as well"--